Fracture testing of existing structures without the need for repairs: - Walters, C.L.; Bruchhausen, M.; Lapetite, J.M.; Duvalois, W. (2017)
It is sometimes necessary to find the toughness of existing structures without damaging them. Examples of this scenario include situations in which the material is suspected of being brittle or service life extensions. However, fracture testing is inherently destructive. Removing material for Charpy or Crack Tip Opening Displacement (CTOD) specimens can result in expensive repairs. The Small Punch Test (SPT), which has been developed for monitoring programs in the nuclear industry, offers a test method that requires such small amounts of material that the test can be performed in a practically non-destructive way. A pilot project was conducted to determine if the SPT can be applied to steels of use in maritime and offshore applications. The results of the pilot project showed that the SPT can identify behavior related to the ductile to brittle transition for an example S355 steel. Therefore, the SPT can provide valuable information for predicting fracture properties relevant to structural-level behavior of steel, such as Charpy transition and estimates of CTOD values in the lower shelf and lower portion of the ductile to brittle transition curve. In the end of this paper, a theoretical framework for transferring results from SPT to CTOD or Charpy testing is outlined.